Management Innovations in International Organizations - Tetenova, Evgeniia; Velinov, Emil; Malý, Milan, 1936-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
Recent studies have shown that traditional management approaches and techniques are not capable of handling a saturated competitive and fast changing environment (Rishipal, 2014). At the same time, most commonly used organizational structures have to be questioned - according to a recent study of Deloitte, most of the companies are not satisfied how their organizational structure functions (Greenfield, 2016). Therefore, this thesis aims to examine the development of modern innovative management methods and practices (including ones which are denoted as Obliquity, Adhocracy, Sociocracy, self-management, etc.) and in practical part it focuses on recently emerged organizational structure called Holacracy. Holacracy is a framework for structuring the organization, it is like an operating system for business that requires the installation of different applications (Knopka Company, 2014; Mint, 2016): for example, applications for hiring employees, for setting salaries, for planning or logistics. Therefore, within the framework of Holacracy, you can apply any other practices such as Lean, Agile or Scrum. For the purpose of this study, the following methods are implemented: the method of qualitative systematic literature review and the analysis of the practices of 97 companies worldwide are summarized and presented in order to critically examine previous research and experience of various companies and, consequently, identify positive and negative elements of Holacracy, its comparison with hierarchy, give suggestions on implementation and create the layout of ideal company for Holacracy.
Vedoucí práce: Emil Velinov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses